2022
DOI: 10.1186/s13014-022-02075-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of radiotherapy plus anti-PD1 versus transcatheter arterial chemoembolization plus sorafenib for advanced hepatocellular carcinoma: a real-world study

Abstract: Background The combination of transcatheter arterial chemoembolization (TACE) plus sorafenib prolonged progression-free survival (PFS) and overall survival (OS) than sorafenib or TACE monotherapy for patients with hepatocellular carcinoma (HCC). This study assessed the efficacy and safety of radiotherapy (RT) plus monoclonal antibody against programmed cell death 1 (anti-PD1) versus TACE plus sorafenib for patients with advanced HCC. Methods Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Meanwhile, RT plus anti-PD1 was associated with a significantly better OS than TACE plus sorafenib among patients with BCLC stage C (11.8 vs 9.7 months, P = 0.031). 13 Similarly, the feasible efficacy evaluation results showed that the ORR of IMRT combined with anti-PD1 was 56.99%, the PR rate was 51.61%, and the CR rate was 5.38%, with an encouraging OS of 14.3 months in the present study. IMRT combined with anti-PD1 seems to have considerable clinical efficacy in the treatment of advanced HCC.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Meanwhile, RT plus anti-PD1 was associated with a significantly better OS than TACE plus sorafenib among patients with BCLC stage C (11.8 vs 9.7 months, P = 0.031). 13 Similarly, the feasible efficacy evaluation results showed that the ORR of IMRT combined with anti-PD1 was 56.99%, the PR rate was 51.61%, and the CR rate was 5.38%, with an encouraging OS of 14.3 months in the present study. IMRT combined with anti-PD1 seems to have considerable clinical efficacy in the treatment of advanced HCC.…”
Section: Discussionsupporting
confidence: 75%
“…The safety of IMRT plus anti -PD1 therapy in this population was consistent with that of RT +PD1 in previously reported studies. 13,14 However, in IMbrave150 study, grade 3 or 4 AEs occurred in 56.5% of patients treated with atezolizumab plus bevacizumab. 6 In summary, no short-term fatal AEs were observed following IMRT and anti-PD1 combination treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have indicated that RT can enhance antitumor immunity when combined with immune checkpoint inhibitors [ 12 ]. RT plus anti-PD1 showed significantly promising efficacy in patients with advanced HCC [ 13 ]. RT alone or combined with other therapies has the potential for tumor downstaging, creating surgical opportunities for more advanced patients [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%